2020
DOI: 10.1111/ffe.13353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contact stress on fretting fatigue behaviour of 35CrMoA steel under multiaxial nonproportional paths

Abstract: Fretting fatigue often occurs in contact couples subjected to both bulk oscillatory loads and normal loads, which accelerates the initiation and propagation of fatigue cracks. This study explores the multiaxial fretting fatigue behaviour of 35CrMoA steel with different contact stresses under diamond and square loading paths by experimental methods. From experimental results, the fracture mechanisms with the increase of contact stress have been summarized by combining the analysis of macrorupture and microruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Due to the fretting wear caused by contact pressure and elliptical loading path, various wear characteristics about fretting fatigue are produced in the fretting zone. Zhou et al (2020) reported that the stick region and slip region on the fretting zone were related to the contact pressure. With increasing contact pressure, the adhesive force between the sample and the fretting pad became stronger, thus reducing the relative displacement, resulting in the fretting zone evolving from gross slip region to partial slip region.…”
Section: Analysis Of Fretting Zone and Wear Debrismentioning
confidence: 99%
“…Due to the fretting wear caused by contact pressure and elliptical loading path, various wear characteristics about fretting fatigue are produced in the fretting zone. Zhou et al (2020) reported that the stick region and slip region on the fretting zone were related to the contact pressure. With increasing contact pressure, the adhesive force between the sample and the fretting pad became stronger, thus reducing the relative displacement, resulting in the fretting zone evolving from gross slip region to partial slip region.…”
Section: Analysis Of Fretting Zone and Wear Debrismentioning
confidence: 99%